Implementation of the Islamic Program to Increase the Religiosity of Students - Mudzakkir; Romlah; Dina Mardiana (Ta'dib, 2024)
This study aims to analyse the implementation of Islamic programs to increase students' religious values at SMP Negeri 4 Pallangga. The problem underlying this study is the importance of instilling religious values ​​early on through religious programs in the school environment. The research method used is a qualitative approach with a field research type. Data collection techniques include interviews, observations, and documentation, while the data analysis method used is descriptive analysis. This study shows that the Islamic religious education program at SMP Negeri 4 Pallangga has succeeded in increasing students' religiosity through structured religious activities, such as congregational prayers, religious lectures, and religious competitions. These activities also shape students' religious character, increasing discipline, concern, and mutual respect. In addition, religious activities strengthen social relationships between students, creating a harmonious environment. Support from teachers, students, and parents and regular evaluation of this program ensure the sustainability and effectiveness of program implementation.